PENGARUH STRUKTUR KEPEMILIKAN, KONTRAK HUTANG DAN KESEMPATAN TUMBUH PADA KONSERVATISME AKUNTANSI - Wulansari, Cahya Agustin (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to test the influence of ownership structure, debt contract, and growth opportunity in conservatism accounting. The samples are manufacturing companies which are listed in Indonesia Stock Exchange. The samples consist of 33 companies which have been selected by using purposive sampling. Multiple linear regression analysis is used as statistics method. The result of the research shows that (1) managerial ownership structure does not have any influence to the conservatism. It is possible since the management tends to focus on maximizing its utility in order to gain high bonus. (2) institutional ownership structure does not have any influence to the conservatism. It is assumed that institutional ownership is only expected on their investment that it has high return rate. (3) debt contract does not have any influence to the conservatism principle. It is possible since the difference of test year that is used in this research interprets the difference of economic condition and the presence of companyâs opportunistic behavior. (4) the growth opportunity does not have any influence to the conservatism. This is caused by the growing company has got good corporate governance. Keywords: managerial ownership structure, institutional ownership structure, debt contract, growth opportunity, and accounting conservatism